Optical CDMA system based on spectral amplitude encoding of incoherent broadband sources. - Adam, Lucie. (University of Ottawa (Canada), 1996)
In this thesis, a new optical Code-Division-Multiple Access (CDMA) system is demonstrated based on spectral amplitude encoding of noncoherent broadband sources. This scheme employs low-cost optical sources such as light-emitting diodes (LEDs). The spreading gain is independent of the data rate, therefore individual users can operate at data rates compatible with available electronic devices. Optical CDMA systems are generally classified into two categories: time-encoded and frequency-encoded systems. In the former case, a low information rate is mapped into a high rate optical pulse sequence. This is possible because of the wide bandwidth of optical fibers. The latter relies on encoding the entire available wavelength band at once with a sequence identifying the intended user. The encoding and decoding principles rely solely upon the crosscorrelation properties exhibited by the set of signals used to distinguish subscribers. We employ simple maximal-length sequences. We demonstrate how data is recovered or rejected with the use of a differential receiver. We examine the transceiver design, and the impact of their characteristics on the system capacity. The performance of the proposed CDMA system is experimentally characterized. The experimental set-up and its advantages and limitations are detailed. We present our bit-error rate (BER) measurements for different code lengths and received power. Also, the resulting eye patterns are shown.
Keywords: Engineering, Electronics and Electrical.